To solve the expression 1/7 - 3(3/7n - 2/7), distribute the 3 to the terms inside the parentheses, simplify the expression inside the parentheses, and combine like terms to get the simplified form of 7n - 1/7.
Explanation:To solve the expression 1/7 - 3(3/7n - 2/7), we need to follow the order of operations which is Parentheses, Exponents, Multiplication and Division (from left to right), and finally Addition and Subtraction (from left to right).
First, distribute the 3 to the terms inside the parentheses: 1/7 - (9/7n - 6/7).
Next, simplify the expression inside the parentheses: 1/7 - 9/7n + 6/7.
Finally, combine like terms by subtracting and adding the fractions: 7n - 1/7.
So, the simplified form of the expression 1/7 - 3(3/7n - 2/7) is 7n - 1/7.
Final answer:
The algebraic expression 1/7 - 3(3/7n - 2/7) can be simplified by distributing the -3 and combining like terms to yield a final expression of 1 - 9/7n.
Explanation:
The student is asking for help in solving an algebraic expression. The problem given is 1/7 - 3(3/7n - 2/7). To solve this, we need to apply the distributive property and then simplify the expression. Here's how we can solve it step by step:
Distribute the -3 to the terms inside the parenthesis: -3 * (3/7)n = -9/7n and -3 * (-2/7) = 6/7.
The expression now becomes 1/7 - 9/7n + 6/7.
Combine like terms, which are the constant fractions: 1/7 + 6/7 = 7/7 = 1.
The final simplified expression is 1 - 9/7n.
The sum of $3,000 is deposited into an account paying 10% annually. If $1,206 is withdrawn at the end of years 1 and 2, how much then remains in the account?"
"The amount remaining in the account after the withdrawals at the end of years 1 and 2 is $1,818.
To solve this problem, we will calculate the amount in the account at the end of each year, taking into account the interest earned and the withdrawals made.
1. At the end of the first year, the account earns 10% interest on the initial $3,000 deposit. The calculation is as follows:
[tex]\[ \text{Amount at the end of year 1}[/tex] = 3000 \times (1 + 0.10) = 3000 \times 1.10 = 3300 \]
2. At this point, $1,206 is withdrawn from the account, leaving:
[tex]\[ \text{Amount after withdrawal at the end of year 1}[/tex]= 3300 - 1206 = 2094 \]
3. This remaining amount then earns 10% interest for the second year:
[tex]\[ \text{Amount at the end of year 2} = 2094 \times (1 + 0.10) = 2094 \times 1.10 \][/tex]
4. At the end of the second year, another $1,206 is withdrawn:
[tex]\[ \text{Amount after withdrawal at the end of year 2} = (2094 \times 1.10) - 1206 \][/tex]
5. To find the exact amount, we calculate the interest earned in the second year and then subtract the withdrawal:
[tex]\[ \text{Interest earned in year 2} = 2094 \times 0.10 = 209.4 \][/tex]
[tex]\[ \text{Amount after interest in year 2} = 2094 + 209.4 = 2303.4 \][/tex]
[tex]\[ \text{Amount after withdrawal at the end of year 2} = 2303.4 - 1206 = 1097.4 \][/tex]
However, there seems to be an error in the calculation. Let's correct it:
[tex]\[ \text{Amount after withdrawal at the end of year 2} = 2094 \times 1.10 - 1206 \][/tex]
[tex]\[ \text{Amount after withdrawal at the end of year 2} = 2303.4 - 1206 \][/tex]
[tex]\[ \text{Amount after withdrawal at the end of year 2} = 1097.4 \][/tex]
This is not the correct final amount. We need to correctly calculate the amount after the second withdrawal:
[tex]\[ \text{Amount after withdrawal at the end of year 2} = (2094 \times 1.10) - 1206 \][/tex]
\[tex][ \text{Amount after withdrawal at the end of year 2} = 2303.4 - 1206 \][/tex]
[tex]\[ \text{Amount after withdrawal at the end of year 2} = 1097.4 \][/tex]
Upon re-evaluating the calculation, we find that the correct amount after the second withdrawal is:
[tex]\[ \text{Amount after withdrawal at the end of year 2} = (2094 \times 1.10) - 1206 \][/tex]
[tex]\[ \text{Amount after withdrawal at the end of year 2} = 2294.4 \][/tex]
[tex]\[ \text{Amount after withdrawal at the end of year 1} = 3300 - 1206 = 2094 \][/tex]
[tex]\[ \text{Amount after withdrawal at the end of year 2} = (2094 \times 1.10) - 1206 = 2294.4 \][/tex]
An isosceles triangle has area of 125 ft. If the base is 16 ft, what is the length of each leg? Round your answer to the nearest tenth
Final answer:
To find the length of each leg of an isosceles triangle with an area of 125 ft² and a base of 16 ft, we first calculate the height and then apply the Pythagorean Theorem. The length of each leg is approximately 17.6 ft.
Explanation:
The question asks about finding the length of each leg of an isosceles triangle given the area and the base. To solve this, we use the formula for the area of a triangle, A = 1/2 × base × height, and apply the Pythagorean Theorem since the height creates a right triangle with the leg of the isosceles triangle and half of the base.
First, we find the height using the given area, A = 125 ft² and base, b = 16 ft. The formula rearranges to height = 2A / base, giving us height = 2(125) / 16 = 15.625 ft.
Next, using the Pythagorean Theorem, a² + b² = c², we let a represent half of the base (8 ft), b be the height (15.625 ft), and c be the leg of the triangle. Solving for c, we find c ≈ 17.6 ft, rounded to the nearest tenth.
Using the graph below, find the missing value to complete the t-chart.
the chart:
x y
-3 5
0 -1
2 ?
A. -3
B. 5
C. 3
D. -5
Answer:
I THINK THE ANSWER IS A
Step-by-step explanation:
BECAUSE IF YOU SEE THEN IT WILL NOT BE B BECAUSE IT WENT DOWN AND IF YOU LOOK IT UP IT WILL BE A
Answer: you answer would be -5
Step-by-step explanation:
Go to the origin and count to the right to places. Then count downwards towards the line and count the number. In this case you move down 5 so it is -5. So count down (or up) towards the line and however many you went that’s your answer (remember up and right are both positive, and down and left are both negative.)
What is the overtime rate for a mail carrier who regularly earns $9.80 an hour?
The overtime rate for a mail carrier earning $9.80 per hour is calculated as one and a half times the regular rate, resulting in an overtime pay of $14.70 per hour.
The question is asking for the overtime rate for a mail carrier earning a regular hourly wage of $9.80. In the United States, the standard overtime rate is typically one and a half times the employee's regular hourly pay for any hours worked beyond 40 in a workweek. Therefore, to calculate the overtime rate for a mail carrier earning $9.80 per hour, the following calculation is performed:
Regular hourly wage times 1.5 = Overtime rate
$9.80 times 1.5 = $14.70 per hour
How do I calculate the volume of a circle?
A circle, being 2-dimensional, does not have volume.
To clarify, a circle is a 2-dimensional shape and therefore does not have a volume. However, if you intended to calculate the volume of a 3-dimensional shape such as a sphere or a cylinder that has a circular base, here are the steps:
Volume of a Cylinder
The formula for the volume of a cylinder is:
V = πr²h
Volume of a Sphere
The formula for the volume of a sphere is:
V = 4/3 πr³
a bag contains 1p 2p and 5p coins .3/8 of the bag are 1p coins.there are as many 5p coins than 1p coins in the bag . there are 640 cois in total. work out the number of 2p coins in the bag
The number of 2p coins in the bag is 160
How to get the number of 2p coins
Assuming:
the number of 1p coins is xthe number of 2p coins is y and the number of 5p coins is z.According to the given information:
x = 3/8 * 640 = 240
z = x = 240
total number of coins is 640.
x + y + z = 640
plugging in the values
240 + y + 240 = 640
y + 480 = 640
y = 160
what are the points of intersection of the lines below 2x-y=10 y=-4x+2
Find the area of a circle circumscribed about an equilateral triangle whose side is 18 inches long.
In triangle XYZ,XY=15,YZ=21, and XZ=27. What is the measure of angle Z to the nearest degree?
Final answer:
Using the Law of Cosines, we find that the cosine of angle Z is approximately 0.6333, and therefore, angle Z in triangle XYZ is approximately 51° when rounded to the nearest degree.
Explanation:
To find the measure of angle Z in triangle XYZ, with sides XY = 15, YZ = 21, and XZ = 27, we can use the Law of Cosines. The Law of Cosines relates the lengths of the sides of a triangle to the cosine of one of its angles. In our case, we can find the cosine of angle Z by the equation:
cos(Z) = (XY² + XZ² - YZ²) / (2 · XY · XZ)
Plugging in the values, we get:
cos(Z) = (15² + 27² - 21²) / (2 · 15 · 27)
Calculating further:
cos(Z) = (225 + 729 - 441) / (810)
cos(Z) = 513 / 810
cos(Z) = 0.6333
The next step is to find the angle whose cosine is 0.6333. We can use a calculator to find the inverse cosine:
Z = cos⁻¹(0.6333)
Hence, the measure of angle Z to the nearest degree is approximately:
Z ≈ 51°
The measure of angle Z is approximately 70 degrees (rounded to the nearest degree).
To find the measure of angle Z in triangle XYZ, you can use the Law of Cosines. The formula is:
[tex]\[ c^2 = a^2 + b^2 - 2ab \cos(C) \][/tex]
where:
- c is the side opposite the angle you want to find (in this case, side XZ),
- a and b are the other two sides (XY and YZ),
- C is the angle opposite side c.
In this case, let C be the angle Z, and a = XY = 15, b = YZ = 21, and c = XZ = 27.
[tex]\[ 27^2 = 15^2 + 21^2 - 2(15)(21) \cos(Z) \][/tex]
Now, solve for cos(Z):
[tex]\[ 729 = 225 + 441 - 630 \cos(Z) \][/tex]
[tex]\[ 630 \cos(Z) = 441 - 225 \][/tex]
[tex]\[ 630 \cos(Z) = 216 \][/tex]
[tex]\[ \cos(Z) = \frac{216}{630} \][/tex]
[tex]\[ \cos(Z) \approx 0.343 \][/tex]
Now, find the angle Z:
[tex]\[ Z = \cos^{-1}(0.343) \][/tex]
[tex]\[ Z \approx 70.18 \][/tex]
So, the measure of angle Z is approximately 70 degrees (rounded to the nearest degree).
Which triangle is it ?
Suppose that Bangladesh, India, Pakistan, and Nepal are economically interdependent. The following table shows the exports and imports of each country, with all monetary values given in millions of equivalent US dollars. Country of Origin Exporting to... Amount ($ 2007-13-04-00-00_files/i0260000.jpg 1,000,000) Bangladesh India 2,817 Bangladesh Pakistan 2,369 Bangladesh Nepal 3,039 India Bangladesh 2,023 India Pakistan 3,462 India Nepal 2,184 Pakistan Bangladesh 3,201 Pakistan India 2,336 Pakistan Nepal 2,338 Nepal Bangladesh 2,707 Nepal India 3,363 Nepal Pakistan 2,332 Based on the information in the table, assuming that these four countries trade strictly within the group, what is the value of the greatest trade balance in this group? a. $841 million b. $847 million c. $8,402 million d. $8,516 million
1. Total trade between Bangladesh and other three nations which are India , Pakistan, Nepal= 2,817 + 2,369 + 3,039=$ 8,225
2. Total trade between India and other three nations which are Bangladesh , Pakistan, Nepal= 2,023 +3,462 + 2,184=$7669
3. Total trade between Pakistan and other three nations which are Bangladesh,India, Nepal=3,201 + 2,336 +2,338= $7875
4. Total trade between Nepal and other three nations which are Bangladesh,India, Pakistan=2,707 +3,363+2,332 = $ 8402
The greatest trade is between Nepal and other three nations which are Bangladesh,India, Pakistan=2,707 +3,363+2,332 = $ 8402→→Option (C)
The following stem-and-leaf plot represents the scores earned by Mr. Roberts's class on their most recent science test.
What is the median of the scores?
78
80
81
86
Answer:
im pretty sure its 81
Step-by-step explanation:
What is 0.0371 × 10000?
at a certain time of day a person 6 ft tall cast a 4 ft shadow how long is the shadow cast by ba 21 ft tree at the same time?
What are two pair fractions with common denominators for 3/5 and 3/4
Tom and Arnold both leave the internet cafe at the same time, but in opposite directions. If Tom travels 9mph and Arnold travels 16mph, how long until they are 200 miles apart?
Which of the following is an odd function?
g(x) = x2
g(x) = 5x – 1
g(x) = 3
g(x) = 4x
Answer:
g(x) = 4x is an odd function.
Step-by-step explanation:
A function g(x) is odd if it satisfies that, for all x we have g(-x) = -g(x). Then,
[tex]g(x) =x^2[/tex] is not an odd function beacuse only give positive values, then for example if x= 2
[tex]g(-2) =(-2)^2 = 4 \neq -4 = -g(2)[/tex].
g(x) = 5x-1 is not an odd function. I'll also give you a counterexample: for x=1 we have
g(-1) = 5(-1)-1 = -6 ≠ -4 = -(5-1) = -g(1).
g(x) = 3 is not an odd function. I'll also give you a counterexample: for x=1 we have
g(-1) = 3 ≠ -3 = -g(1).
Finally, g(x) = 4x is an odd function because for all x we have g(-x) = -g(x):
g(-x) = 4(-x) = -4x = -g(x).
What can be determined about this data set before finding the range or the interquartile range? 19, 25, 35, 38, 41, 49, 50, 52, 99
The data has an outlier, but the interquartile range will not change. The answer is c
Please answer this question and give give a detailed answer. Brainliest to who ever answers first and gets it correct
Assume the method dosomething has been defined as follows: public static void dosomething (int[] values, int p1, int p2) { int temp = values[p1]; values[p1] = values[p2]; values[p2] = temp; } what does the method do?3
donna received a $70 gift card for a coffee store. she used it in buying some coffee that cost $7.84 per pound. after buying the coffee, she had $30.80 left on her card. how many pounds of coffee did she buy?
a population of 140000 grows 4% per year for 16 years. How much will the population be after 16 years?
the longest side of an acute isosceles triangle is 8 centimeters . rounded to the nearest tenth, what is the smallest possible length of one of the two congruent sides?
Answer:5.7 cm
Step-by-step explanation:
Just took the test.
what is the maximum volume of water a hamster bath can hold with a depth of 1 2/3, a length of 2 1/3 inches, and a width of 2 inches?
Answer:
[tex]V=7\frac{7}{9} cubic inches[/tex]
Step-by-step explanation:
Given: The length of the hamster bath is [tex]2\frac{1}{3}[/tex] inches, width is 2 inches and the depth is [tex]1\frac{2}{3}[/tex] inches.
To find: The maximum volume of water a hamster bath can hold.
Solution: It is given that The length of the hamster bath is [tex]2\frac{1}{3}[/tex] inches, width is 2 inches and the depth is [tex]1\frac{2}{3}[/tex] inches, then the volume is given as:
[tex]V=l{\times}w{\times}d[/tex]
Substituting the given values, we have
[tex]V=2\frac{1}{3}{\times}2{\times}1\frac{2}{3}[/tex]
[tex]V=\frac{7}{3}{\times}2{\times}\frac{5}{3}[/tex]
[tex]V=\frac{70}{9}[/tex]
[tex]V=7\frac{7}{9} cubic inches[/tex]
Therefore, the maximum volume is [tex]7\frac{7}{9} cubic inches[/tex].
What is the order of 5x10^4 , 7x10^-5 , 3x10^-9 , 8x10^4 from least to greatest?
Answer:
[tex]3\times10^{-9},7\times 10^{-5},5\times 10^4,8\times10^4[/tex]
Step-by-step explanation:
We want to order ; [tex]5\times 10^4,7\times 10^{-5},3\times10^{-9},8\times10^4[/tex] from least to greatest.
Observe that all these numbers are in standard form.
We can order them based on the exponents.
[tex]-9<\:-5<\:4[/tex]
Since two numbers have the same exponent of 4, we need to use the multiplier to order the last two(5<8).
From least to greatest we have;
[tex]3\times10^{-9}\:<\:7\times 10^{-5}\:<\:5\times 10^4\:<\:8\times10^4[/tex]
The numbers in ascending order from least to greatest are 3x10²-9, 7x10²-5, 5x10²4, 8x10²4
To order the numbers from least to greatest, to compare the values of the numbers without the powers of 10 first and then consider the powers of 10.
Given numbers:
5x10²
7x10²-5
3x10²-9
8x10²4
Step 1: Compare the numbers without the powers of 10:
The numbers without the powers of 10 are: 5, 7, 3, and 8.
Step 2: Arrange the numbers in ascending order based on their values:
3, 5, 7, 8
Step 3: Now, consider the powers of 10:
The powers of 10 are: 10²4, 10²-5, 10²-9, and 10²4.
Since all the powers of 10 are positive, larger powers of 10 indicate larger numbers.
Step 4: Combine the results from Steps 2 and 3 to get the final order:
3x10²-9, 7x10²-5, 5x10²4, 8x10²4
To know more about ascending here
https://brainly.com/question/30325384
#SPJ6
NEED HELP ASAP!!!!!!!!
Kareem lives 4/10 of mile from the mall.Write two equivalent fraction that show what fraction of mile Kareem lives from the mall
Emma is going camping. Each side triangle on her tent is 5 feet tall. The square base is 4 feet wide. What is the surface area of her tent?
What equation results from completing the square and then factoring? x^2 + 24x = 33
Answer:
[tex](x+12)^2=177[/tex]
Step-by-step explanation:
We have been given an equation: [tex]x^2+24x=33[/tex].
To complete the square we change the left hand side of the equation to a perfect square trinomial. For this we add [tex](\frac{b}{2})^2[/tex] to both sides of equation, where b is the coefficient of x.
We can see that coefficient of x for our given equation is 24. So we will add [tex](\frac{24}{2})^2=12^2=144[/tex] to both sides of our equation.
[tex]x^2+24x+144=33+144[/tex]
[tex]x^2+24x+144=177[/tex]
Let us factor left side of our equation as the square of binomial.
[tex](x+12)^2=177[/tex]
Therefore, our resulting equation will be [tex](x+12)^2=177[/tex].
Answer: (x+12)^2=177
Step-by-step explanation:
What are the intercepts of the line?
A.
x-intercept:-8 ; y-intercept:0
B.
x-intercept:0 ; y-intercept:
C.
x-intercept:-8 ; no y-intercept:
D.
no x-intercept: ; y-intercept:-8
Answer:
D cause it crosses at -8
Step-by-step explanation: